Implication of multivalent aptamers in DNA and DNA-RNA hybrid structures for efficient drug delivery in vitro and in vivo - Kang, Yoon Young; Song, Jihyeon; Jung, Hee Sun; Kwak, Gijung; Yu, Gyeonghui; Ahn, Joong-Hoon; Kim, Sun Hwa; Mok, Hyejung (한국공업화학회, 2018)
To examine proper multivalency and type of aptamers in linear nucleic acid-based structures for efficient intracellular uptakes, we designed linear DNA structures with single and dual aptamers targeting guanosine-rich oligonucleotide 100 (AS1411) and mucin 1 (MUC-1). Multivalent linear DNA structures containing dual types of aptamers showed significantly superior cellular internalization. In addition, multivalent aptamer-immobilized DNA-RNA hybrid structures showed excellent tumor accumulation in vivo without liver toxicity and very low nonspecific cytokine induction. Thus, these multivalent nucleic acid based structures with dual types of aptamers can be specifically applied as carriers of therapeutic nucleic acids without inducing noticeable systemic toxicity. (C) 2017 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.